Evaluation of Peak Inspiratory Flow Rate in Hospitalized Palliative Care Patients with COPD - Joshua Borris; Heather Cook; Sulgi Chae; Kathryn A. Walker; Mary Lynn McPherson (MDPI AG, 2023)
Dry powder inhalers are an effective yet costly COPD medication-delivery device. Patients must possess a minimum peak inspiratory flow rate (PIFR) for inhaled medication to be properly deposited into the lungs. Hospitalized palliative-care patients with diminished lung function due to advanced COPD may not possess the minimum PIFR (30 L/min) for adequate drug delivery. This study aims to quantify PIFR values for hospitalized palliative-care patients with advanced COPD to evaluate whether these patients meet the minimum PIFR requirements. Hospitalized patients ≥18 years old with a palliative-care consultation were eligible if they had a diagnosis of advanced COPD (GOLD C or D). Patients were excluded if they lacked decision-making capacity or had a positive COVID-19 test within the previous 90 days. Three PIFR values were recorded utilizing the In-CheckTM device, with the highest of the three PIFR attempts being utilized for statistical analysis. Eighteen patients were enrolled, and the mean of the highest PIFR readings was 72.5 L/min (±29 L/min). Post hoc analysis indicated 99.9% power when comparing the average best PIFR to the minimum PIFR (30 L/min) but only 51.4% power when compared to the optimal PIFR (60 L/min). This study found that palliative-care patients possess the minimum PIFR for DPI drug delivery.